GE_GERICHTE C/12057/2013 vom 23. November 2015 - GE Cour de justice (2015)
BAIL À LOYER; CONTESTATION DU CONGÉ; MOTIF; SOUS-LOCATION; PROLONGATION DU BAIL À LOYER; PESÉE DES INTÉRÊTS | CO.266; CO.271; CO.271a; CO.272